Understanding ESP Learners’ Views on the Importance of the Four Language Skills in Professional and Business Settings - Abdullah Kafabih; Rozanah Katrina Herda; Zohaib Hassan Sain (Journal of General Education and Humanities, 2026)
This study investigates how English for Specific Purposes ESP learners’ view on the importance of the four macro-skills: speaking, reading, writing and listening in professional and business settings among Indonesian university learners. Despite widespread recognition of English as a key medium in global workplaces, empirical evidence regarding students’ prioritisation of these skills remains limited, particularly in Indonesia. A quantitative survey was conducted among 47 university learners enrolled in ESP programs employing a structured questionnaire with a four-point Likert scale to capture perceptions across the four skill areas. The sample was selected using purposive sampling, and the questionnaire had been reviewed through expert validation to ensure content appropriateness. Descriptive statistical analyses showed that reading had the highest mean score (3.553), followed by speaking (3.547), writing (3.542), and listening (3.516), indicating consistently high perceived importance across all four macro skills. The findings underscore the need for ESP curricula to integrate all four skills and cohesively align instructional practices with workplace expectations. This study contributes to the literature by providing a holistic view of learners' views on English macro-skill importance and offers practical implications for curriculum designers and educators seeking to enhance learners’ readiness for global professional communication.